2019
DOI: 10.2514/1.a34056
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Assessment of Aerocapture and Applications to Future Missions

Abstract: We examine the current state of readiness of aerocapture at several destinations of interest, to identify what technologies are needed and to determine if a technology demonstration mission is required, before the first use of aerocapture for a science mission. The study team concluded that the current state of readiness is destination dependent, with aerocaptured missions feasible at Venus, Mars, and Titan with current technologies. The use of aerocapture for orbit insertion at the ice giant planets Uranus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…Studies over several decades have shown that the technical risks associated with aerocapture can be mitigated, for example many of the technologies a future aerocapture vehicle would use such as guided hypersonic flight has been demonstrated by Apollo and Mars Science Laboratory (MSL). 12 The cost and schedule risks for aerocapture are substantially less understood, along with programmatic and political risks. The present study recommends that future aerocapture studies apply quantitative risk assessment techniques which NASA has matured though numerous manned and robotic missions.…”
Section: Subsystem Design Cost and Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies over several decades have shown that the technical risks associated with aerocapture can be mitigated, for example many of the technologies a future aerocapture vehicle would use such as guided hypersonic flight has been demonstrated by Apollo and Mars Science Laboratory (MSL). 12 The cost and schedule risks for aerocapture are substantially less understood, along with programmatic and political risks. The present study recommends that future aerocapture studies apply quantitative risk assessment techniques which NASA has matured though numerous manned and robotic missions.…”
Section: Subsystem Design Cost and Risk Assessmentmentioning
confidence: 99%
“…13 A recent study initiated by the NASA Planetary Science Division concluded that a technology demonstration mission is not required before use of aerocapture on a mission, but remarks that ice giants require additional study. 12 Quantitative cost and risk estimate for an ice giant aerocapture mission concept is highly desired and will inform the upcoming Decadal survey studies regarding the readiness of its use for a large strategic mission.…”
Section: Subsystem Design Cost and Risk Assessmentmentioning
confidence: 99%
“…since the last such study was performed could allow the navigation uncertainty component to be reduced and hence lower the vehicle L/D requirement. Atmospheric uncertainties at Neptune have been modeled in Neptune-Global Reference Atmospheric Model (GRAM), but no improvements are available over the data used by Lockwood et al 1 Spilker et al 4 recommends performing opportunistic stellar occultations of Uranus and Neptune to improve the atmospheric models, but also notes that the technique may only provide information at high altitudes and extrapolating to altitudes relevant to aerocapture carries greater uncertainties. A dedicated research program for combined ground-based observations and modeling efforts is required to reduce the atmospheric uncertainties at altitudes relevant to aerocapture.…”
Section: Mission Designmentioning
confidence: 99%
“…The large navigation and atmospheric uncertainties drive the need for a vehicle with sufficient control authority to perform aerocapture without the spacecraft risking escape or getting trapped in the atmosphere. 4 Several mission concepts and technology demonstration flights have proposed the use of aerocapture, but have never been flown. [5][6][7][8][9] Hall et al 10 showed that aerocapture could enhance missions to Venus, Mars, Titan, and Uranus and enable some missions to Jupiter, Saturn, and Neptune.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation